Recovery after caesarean birth: a qualitative study of women's accounts in Victoria, Australia - Kealy Michelle A; Small Rhonda E; Liamputtong Pranee (BMC, 2010)
Abstract Background The caesarean section rate is increasing globally, especially in high income countries. The reasons for this continue to create wide debate. There is good epidemiological evidence on the maternal morbidity associated with caesarean section. Few studies have used women's personal accounts of their experiences of recovery after caesarean. The aim of this paper is to describe women's accounts of recovery after caesarean birth, from shortly after hospital discharge to between five months and seven years after surgery. Method Women who had at least one caesarean birth in a tertiary hospital in Victoria, Australia, participated in an interview study. Women were selected to ensure diversity in experiences (type of caesarean, recency), caesarean and vaginal birth, and maternal request caesarean section. Interviews were audiotaped and transcribed verbatim. A theoretical framework was developed (three Zones of clinical practice) and thematic analysis informed the findings. Results Thirty-two women were interviewed who between them had 68 births; seven women had experienced both caesarean and vaginal births. Three zones of clinical practice were identified in women's descriptions of the reasons for their first caesareans. Twelve women described how, at the time of their first caesarean section, the operation was performed for potentially life-saving reasons (Central Zone), 11 described situations of clinical uncertainty (Grey Zone), and nine stated they actively sought surgical intervention (Peripheral Zone). Thirty of the 32 women described difficulties following the postoperative advice they received prior to hospital discharge and their physical recovery after caesarean was hindered by a range of health issues, including pain and reduced mobility, abdominal wound problems, infection, vaginal bleeding and urinary incontinence. These problems were experienced across the three zones of clinical practice, regardless of the reasons women gave for their caesarean. Conclusion The women in this study reported a range of unanticipated and unwanted negative physical health outcomes following caesarean birth. This qualitative study adds to the existing epidemiological evidence of significant maternal morbidity after caesarean section and underlines the need for caesarean section to be reserved for circumstances where the benefit is known to outweigh the harms.